STUDI KOMPARASI PEMBERIAN KREDIT PKM TERHADAP PENINGKATAN DAYA SAING USAHA KECIL SEPATU DALAM MENGHADAPI SERBUAN PRODUK CINA DI KABUPATEN SIDOARJO - Sigit Hermawan; Rifdah Abdiyah; Wisnu P Setiyono (EKUITAS (Jurnal Ekonomi dan Keuangan), 2008)
The objectives of the study are: (1) to identify the capital resources obtained by the shoes small businesses that get KPKM and those that do not in order to increase the competitive ability to cope with the Chinese products rush; (2) to compare the capital resources between the shoes small businesses that get KPKM and those that do not to cope with the Chinese products rush; and (3) to compare the competitive ability of the shoes small business that get KPKM and those that do not to cope with the Chinese products rush.The results of the study are: (1) the respondents have had various capital resources on the average, so that they do not only rely on the internal capital resources but also the external capital resources. Yet, most of them do not take the external capital resources from the legal organization, such as financial foundations, banks, and credit programs; (2) there is no real difference between UKM that has the capital resources for the shoes small business which get KPKM and those which do not; and (3) UKMs on the average are able to compete to cope with the Chinese products rush.